(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: firstly To assess the incidence of Corona Virus -19 covid-19 as risk factors in obese individuals leading to thrombotic episode, and secondly to compare the effects Plasminogen activator inhibitor-1 (PAI-1) on the occurrence of this thrombotic status in obese and normal body weight individuals. The pathogenesis of Coronavirus disease 2019 (COVID-19) is gradually demonstrated and explained around the world A high and a great number of thrombotic episodes are reported, in present study can be consider the COVID-19 as a prothrombotic disease. Design and Methods: The experiments comparing the PAI-1 in 90 obese and 30 normal body weight participants aged 32-62 years. The obese patients subdivided to three groups: first group consisted from 30 over weight individuals and the second group comprised from 30 obese patients, while third group consisted from 30 morbid obesity patients. All participants underwent to the medical examinations to make sure they were infected with covid-19. The activity of PAI-1and tissue plasminogen activator (t-PA) was determined by applied ELISA method by certain kit in all study groups individuals. Results: Three study groups (overweight, obese, and morbid obesity) elicited significant (p< 0.05) elevation in metabolic characteristics such as fasting blood glucose (FBG), fasting insulin and lipids variables, as well as increasing in insulin resistance (HOMA-IR) and D-dimer fractions, in addition to there were significant augmentation in PAI-1 and t-PA in three study groups when comparing with those of normal or healthy body weight The present results show a positive relationship between PAI-1 and body mass index, t-PA, D-dimer and metabolic characteristics which include fasting blood glucose, fasting insulin and lipids fractions, also HOMA-IR.